ANALYSIS OF ANTIHYPERTENSION THERAPY IN HYPERTENSION BPJS PATIENTS IN PURBALINGGA DISTRICT - Khamdiyah Indah K, (Jurnal Cakrawala Ilmiah, 2022)
Hypertension is a problem in the world because hypertension is one of the entry points for other disease risk factors. According to basic health research data (Rikesdar, 2018) the incidence of hypertension cases is 34.1%. According to the Purbalingga Health Office, the number of cases of hypertension in 2017 was 1,252 cases (14.26%) of 144,633 people aged 18 who had high blood pressure measured at the puskesmas and its network. Each antihypertensive drug will always show a different effect on blood pressure patient. This research was conducted to find out the therapeutic profile of single and combination drugs, to compare the effectiveness of reducing blood pressure and the relationship between reducing blood pressure and research factors. This research is a descriptive study by looking at the patient's blood pressure profile in medical records for 4 consecutive months in hypertensive patients in Purbalingga. Data were tested using the Kruskall-Wallis test followed by Mann-Whitney and also the Cross tab test. The results showed that out of 108 patients, 75 patients (69.4%) received single therapy consisting of the Chalcium Chanel Blocker (CCB) group of 72 patients (96%) and the Angiotensin-Converting Enzym Inhibitor (ACEI) group of 3 patients ( 4%) . Combination therapy in 8 patients (7.46%) with CCB + ACEI as the treatment group, then 25 patients (23.14%) received therapy that changed groups. Compliance in patients receiving CCB therapy, out of 72 patients who routinely took drugs, 60 patients (83.3%), 45 patients (62.5%) went on a diet, and 20 patients (27.8%) complained of symptoms. The effectiveness of CCB group therapy was able to reduce BP according to the target in 39 patients (54.1%). The combination of CCB +ACEI was able to reduce BP according to the target in 4 patients (50%).